Early Joint Replacement in Juvenile Idiopathic Arthritis: Trend Over Time and Factors Influencing Implant Survival. Issue 9 (2nd August 2021) - Marino, Achille; Pontikaki, Irene; Truzzi, Marcello; Menon, Alessandra; Artusi, Carolina; Di Marco, Marco; Randelli, Pietro S.; Cimaz, Rolando; Viganò, Roberto
Abstract : Objective: To describe early prosthesis implantations in a cohort of patients with juvenile idiopathic arthritis (JIA) followed in a tertiary referral hospital and to analyze possible factors influencing implant survival. Methods: This was a retrospective cohort study. Charts of all patients with JIA who underwent total joint replacement at Gaetano Pini Hospital, Milan, Italy from January 1992 to June 2019 were retrieved, and relevant data were analyzed. Results: Eighty‐five patients met the inclusion criteria for this study, with a median follow‐up period of 17.2 years. The median age at first prosthesis was 22.7 years. The total number of replaced joints was 198 over a period of 27 years. The hip was the most frequently replaced joint, accounting for almost two‐thirds of the total number of implants; the other one‐third refers mostly to knee implants. Polyarticular JIA and systemic JIA were the most represented JIA categories in the study cohort. A significant upward trend of the age at arthroplasty and of disease duration before arthroplasty over decades was found. The rates of implant survival at 5, 10, and 15 years were comparable (from 84% to 89%); 50% of implants lasted ≥20 years. Conclusion: We reported retrospective data on early joint replacement in a cohort of patients with JIA. We observed a progressive and significant upward trend of both age at arthroplasty and disease duration before the first arthroplasty over time. The JIA category, year of implant, and presence of complications significantly affected implant survivorship.